THE ADVANTAGES OF IMPLEMENTATION OF INTEGRATED MANAGEMENT SYSTEM ON ISO45001, AND ISO14001 IN MANUFACTURING INDUSTRY - Pratikno, Yuni; Kusnadi (Dinasti International Journal of Digital Business Management, 2020)
Integrated management system (IMS) can integrate several management systems in companies such as: Environmental Management Systems (ISO 14001) and Occupational Health and Systems Safety Management (ISO45001). The purpose of this study is to answer the question of what and how to implement IMS policies in industrial companies in the fields of occupational safety, occupational health and environmental sustainability. This IMS implementation research was conducted on a manufacturing industry that has implemented IMS. The research method is conducted with qualitative methods with CIPP evaluative model (Context, Input, Process, and Product). This study succeeded in uncovering the implementation of IMS in the manufacturing industry which was investigated that the IMS had been fully implemented in the Occupational Health and Environmental Management and Safety System (HSE). The IMS is implemented at the policy level or management commitment (context), HSE planning (Input), operational implementation (process), HSE monitoring and evaluation and a review (Product) for continuous performance improvement.